MULTIMODAL MEMORY AND INTERTEXTUALITY IN BHUKAR XAADHU: A MYTH OF HUNGER_A MYTH OF HUNGER_A MYTH OF HUNGER BY DR. MRINAL JYOTI GOSWAMI: FROM CARROLL’S WONDERLAND TO CONTEMPORARY ABUSE - Phukan, Nakul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Bhukar Xaadhu: A Myth of Hunger: A Myth of Hunger, written and directed by Dr. Mrinal Jyoti Goswami, is a compelling experimental performance that fuses visual, textual, and performative media to interrogate multiple forms of hunger—biological, political, psychological, and sexual. This paper explores the play as a site of multimodal memory, where iconic images such as The Vulture and the Little Girl and Napalm Girl, alongside textual allusions from Lewis Carroll’s Alice in Wonderland and Through the Looking Glass, function as intertextual anchors that provoke ethical, emotional, and aesthetic reflection. Using Linda Hutcheon’s theory of intertextuality, Marianne Hirsch’s concept of postmemory, and Peggy Phelan’s notion of the unmarked in performance, this study analyzes how the play constructs an affective dramaturgy that oscillates between historical trauma and poetic imagination. The sculptor figure in the play operates as both artist and witness, navigating through a fragmented landscape of visual journalism, children’s rhymes, and surreal dreamscapes. The performance’s layering of absurdity with real-world atrocities challenges conventional boundaries between fiction and documentary, past and present, visibility and silence. In doing so, Bhukar Xaadhu: A Myth of Hunger emerges as a powerful theatrical meditation on the politics of representation and the haunting persistence of memory.